Urocortin-2 Prevents Dysregulation of Ca2+ Homeostasis and Improves Early Cardiac Remodeling After Ischemia and Reperfusion - Domínguez-Rodríguez, Alejandro; Mayoral-Gonzalez, Isabel; Avila-Medina, Javier; de Rojas-de Pedro, Eva S.; Calderón-Sánchez, Eva; Díaz, Ignacio; Hmadcha, Abdelkrim; Castellano, Antonio; Rosado, Juan A.; Benitah, Jean-Pierre; Gomez, Ana M.; Ordoñez, Antonio; et al. (Frontiers in Physiology, 2018)
Aims: Urocortin-2 (Ucn-2) is a potent cardioprotector against Ischemia and Reperfusion (I/R) injuries. However, little is known about its role in the regulation of intracellular Ca2+ concentration ([Ca2+]i) under I/R. Here, we examined whether the addition of Ucn-2 in reperfusion promotes cardioprotection focusing on ([Ca2+]i handling. Methods and Results: Cardiac Wistar rat model of I/R was induced by transient ligation of the left coronary artery and experiments were conducted 1 week after surgery in tissue and adult cardiomyocytes isolated from risk and remote zones. We observed that I/R promoted significant alteration in cardiac contractility as well as an increase in hypertrophy and fibrosis in both zones. The study of confocal [Ca2+]i imaging in adult cardiomyocytes revealed that I/R decreased the amplitude of [Ca2+]i transient and cardiomyocytes contraction in risk and remote zones. Interestingly, intravenous infusion of Ucn-2 before heart’s reperfusion recovered significantly cardiac contractility and prevented fibrosis, but it didn’t affect cardiac hypertrophy. Moreover, Ucn-2 recovered the amplitude of [Ca2+]i transient and modulated the expression of several proteins related to [Ca2+]i homeostasis, such as TRPC5 and Orai1 channels. Using Neonatal Rat Ventricular Myocytes (NRVM) we demonstrated that Ucn-2 blunted I/R-induced Store Operated Ca2+ Entry (SOCE), decreased the expression of TRPC5 and Orai1 as well as their interaction in reperfusion. Conclusion: Our study provides the first evidences demonstrating that Ucn-2 addition at the onset of reperfusion attenuates I/R-induced adverse cardiac remodeling, involving the [Ca2+]i handling and inhibiting the expression and interaction between TRPC5 and Orai1.